Dyscalculia in Learning Mathematics: Underpinning Concerns for Delivering Contents - Kunwar, Rajendra (Dristikon: A Multidisciplinary Journal, 2021)
Dyscalculia is a term that affects the ability to acquire arithmetical skills. It is one of the important areas of a specific learning disorder in mathematics covering the areas particularly, number sense, memorization of arithmetic facts, accurate and fluent calculation, and accurate math reasoning. It is estimated that about 3-6 percent of the population is facing problems associated with dyscalculia. This paper explores the theoretical consideration of dyscalculia in learning mathematics and outlines the ways of employing effective pedagogy to address dyscalculic students. The study is based on theoretical and descriptive methods. It focuses on the theoretical concern about learning mathematics, dyscalculia, its meaning and concept, types, causes, common difficult areas and impacts on mathematics learning. It also draws out the way of effectively delivering content and provides support for the dyscalculic learner. This article concludes that dyscalculic learners are facing various difficulties due to their weak number sense, low basic mathematics fluency, reasoning and accurate arithmetic calculation. Thus it is essential to provide specialized instruction as well as extra support to uplifts and retain the skills and performance of the dyscalculic learner in mathematics. Otherwise, the arithmetic inability can lead the learner to more difficult circumstances that may be beyond the classroom learning context.